Application of the Sponge Model Implants in the Study of Vaccine Memory in Mice Previously Immunized with LBSap - Mariana Ferreira Lanna; Lucilene Aparecida Resende; Paula Mello De Luca; Wanessa Moreira Goes; Maykelin Fuentes Zaldívar; André Tetzl Costa; Walderez Ornelas Dutra; Alexandre Barbosa Reis; Olindo Assis Martins-Filho; Kenneth Jhon Gollob; Sandra Aparecida Lima de Moura; Edelberto Santos Dias; et al. (Vaccines)
Background/Objectives: Considering the large number of candidates in vaccine-testing studies against different pathogens and the amount of time spent in the preclinical and clinical trials, there is a pressing need to develop an improved in vivo system to quickly screen vaccine candidates. The model of a polyester–polyurethane sponge implant provides a rapid analysis of the specific stimulus–response, allowing the study of a compartmentalized microenvironment. The sponge implant’s defined measurements were standardized as a compartment to assess the immune response triggered by the vaccinal antigen. The LBSap vaccine (composed of Leishmania braziliensis antigens associated with saponin adjuvant) was used in the sponge model to assess the antigen-specific immunological biomarker, including memory generation after initial contact with the antigen. Methods: Mice strains (Swiss, BALB/c, and C57BL/6) were previously immunized using LBSap vaccine, followed by an antigenic booster performed inside the sponge implant. The sponge implants were assessed after 72 h, and the immune response pattern was analyzed according to leukocyte immunophenotyping and cytokine production. Results: After LBSap vaccination, the innate immune response of the antigenic booster in the sponge implants demonstrated higher levels in the Ly+ neutrophils and CD11c+ dendritic cells with reduced numbers of F4/80+ macrophages. Moreover, the adaptive immune response in Swiss mice demonstrated a high CD3+CD4+ T-cell frequency, consisting of an effector memory component, in addition to a cytoxicity response (CD3+CD8+ T cells), displaying the central memory biomarker. The major cell surface biomarker in the BALB/c mice strain was related to CD3+CD4+ effector memory, while the increased CD3+CD8+ effector memory was highlighted in C57/BL6. The cytokine profile was more inflammatory in Swiss mice, with the highest levels of IL-6, TNF, IFN-g, and IL-17, while the same cytokine was observed in in C57BL/6 yet modulated by enhanced IL-10 levels. Similar to Swiss mice, BALB/c mice triggered an inflammatory environment after the antigenic booster in the sponge implant with the increased levels in the ILL-6, TNF, and IFN-g. Conclusions: The findings emphasized the impact of genetic background on the populations engaged in immune responses, suggesting that this model can be utilized to enhance and track both innate and adaptive immune responses in vaccine candidates. Consequently, these results may inform the selection of the most suitable experimental model for biomolecule testing, taking into account how the unique characteristics of each mouse strain affect the immune response dynamics.